Bioimperialismo e direito de propriedade intelectual: disputas pelo acesso ao cupuaçu e ao conhecimento tradicional - Ferreira, Juliana da Paz Sousa [UNESP] (2015)
Disputes over access to biodiversity and traditional knowledge in Brazil, are not resolved very simply, with a view that it is not only to guarantee the right of trademarks and patents, for scientists and entrepreneurs of multinationals in both production biotechnology, as the industrial-scale production. The problem lies mainly in the way of monopolistic ownership of both biological resources, knowledge as applied to them, resulting in the practice of biopiracy and socio-environmental degradation. Moreover, intangible assets are increasingly important to the strategies of large firms. It is therefore related conflicts: the sovereignty and the national and international regulation. To demonstrate the mechanisms, conflicts, legal aspects, social aspects, the specific benefits in dispute, the question of the preservation of biodiversity and the livelihoods of indigenous and traditional communities, the competition for cupuaçu was studied from 2002 to 2012.